Les compétences tunisiennes à l’étranger : peut-on parler d’une diaspora scientifique ? - Lotfi Slimane; Wafa Khlif (L’Année du Maghreb)
Migratory dynamics are strongly marked by the globalization of national economies whose competitiveness would be better measured in terms of a mobilized “capital of competencies”. This notion of “competence abroad” forms the basis for a scientific diaspora. However the implication of the latter for the development of the country of origin is marked by ambivalence. Empirical results show an array of obstacles explaining the limited engagement of expatriated Tunisian competencies. The scientific and technical competencies of the Tunisian diaspora did not meet with the conditions necessary for the emergence of a real diaspora. Cultural, organizational and administrative impediments associated with the absence of a clear and well defined governmental vision constitute the most important obstacle to their implication.